2022
DOI: 10.1177/0261927x221137581
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Look at the “Invisibility” of Older Gay Men Within the Categories ‘Gay Man’ and ‘Elderly Man’

Abstract: Two studies analyzed whether, at the cognitive level, ‘Elderly gay man’ is “invisible” both when processing the labels ‘Gay man’ and ‘Elderly man’. We suggest that ‘Gay man’ is conflated with ‘Young man’, and that ‘Elderly man’ is conflated with ‘Heterosexual man’. Contact with elderly gay men did not alter the perception of ‘Gay man’ as prevalently young but weakened the perception of ‘Elderly man’ as heterosexual by default.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Replicating previous findings, albeit with a different measure, Study 1 showed that participants perceived 'heterosexual men' as equally typical of both young and elderly men, while they viewed 'gay men' as more typical of young than of elderly men (e.g. Carnaghi et al, 2022;Coladonato et al, 2023). These results suggest that the category 'heterosexual men' is uncorrelated with age categories and is likely to comprise instances of both ages.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Replicating previous findings, albeit with a different measure, Study 1 showed that participants perceived 'heterosexual men' as equally typical of both young and elderly men, while they viewed 'gay men' as more typical of young than of elderly men (e.g. Carnaghi et al, 2022;Coladonato et al, 2023). These results suggest that the category 'heterosexual men' is uncorrelated with age categories and is likely to comprise instances of both ages.…”
Section: Discussionsupporting
confidence: 71%
“…However, no data on the age stereotyping of female sexual orientation categories as well as on the sexual orientation stereotyping of female age categories are currently available. In contrast, recent work by Carnaghi et al (2022) and Coladonato et al (2023) indicate that people use stereotypical traits that evoke young versus old age equally to characterize 'heterosexual men'. That is, the category 'heterosexual men' tends to be, at least in part, uncorrelated with age categories.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Through that, research by means of the otherwise well-validated "Who said what?" paradigm has become somewhat disbanded from research on asymmetrical categorization that investigates marked versus unmarked categories (Hegarty & Pratto, 2001), invisible categories (Coladonato et al, 2023;Sesko & Biernat, 2010), or figure-ground asymmetries in categorization (Rothermund & Wentura, 2001). Knowing that a single-presentation "Who said what?"…”
Section: Discussionmentioning
confidence: 99%
“…For example, common (published) research questions tackled by means of this paradigm often ask whether people categorize others by a certain category dimension at all, whether an independent variable reduces or increases categorization by a certain category dimension, or how categorization by one dimension influences categorization by another dimension (e.g., Flade et al, 2019; Heidrich et al, 2024; Klapper et al, 2016; Klauer et al, 2014). Through that, research by means of the otherwise well-validated “Who said what?” paradigm has become somewhat disbanded from research on asymmetrical categorization that investigates marked versus unmarked categories (Hegarty & Pratto, 2001), invisible categories (Coladonato et al, 2023; Sesko & Biernat, 2010), or figure-ground asymmetries in categorization (Rothermund & Wentura, 2001). Knowing that a single-presentation “Who said what?” task may be able to reproduce asymmetrical categorization strengths for different categories such as Black or White along the same dimension—race, in this case—may make the “Who said what?” paradigm accessible to these branches of social categorization research.…”
Section: Discussionmentioning
confidence: 99%